Method for fixed-point preparation of polycrystalline silicon microstructure characterization sample
Through the combined process of mechanical polishing, ion polishing and micron-level fixed-point ion polishing, the problem of microstructure observation and lossless surface effect of polycrystalline silicon characterization sample preparation is solved, and the efficient preparation of polycrystalline silicon microstructure characterization sample is achieved.
Patent Information
- Application Number
- CN202411426019.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-03
AI Technical Summary
The existing polysilicon characterization sample preparation technology, especially polishing methods, is difficult to meet the observation of microstructures at specific locations in polysilicon, and it is difficult to obtain surface effects in a lossless state.
Using a combination of mechanical polishing, ion polishing and micron-scale fixed-point ion polishing, the fixed-point polishing of the sample surface is achieved by polishing using diamond and silica polishing liquid, and thick and thinning of ion under a multi-beam focused ion beam electron microscope. .
Observation samples in a completely lossless state are obtained, which can meet the microstructure observations at specific locations, especially the microstructure presentation at the interface of polycrystalline silicon matrix-silicon core, thus solving the problem that the microstructure observations and lossless surface effects in the prior art cannot meet the microstructure observations and lossless surface effects at specific locations. The problem.
Smart Images

Figure CN119246193A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polysilicon sample preparation, and in particular relates to a method for preparing a polysilicon microstructure characterization sample at a fixed point. Background Art
[0002] Microscopic observation of polysilicon is an important basis for studying the relationship between polysilicon quality and microstructure. In addition, there are many important interfaces for polysilicon, such as the interface between the substrate and the silicon core. The observation of the microstructure at this interface is also a crucial step in understanding the relationship between polysilicon quality and microstructure. Existing preparation technologies for polysilicon characterization samples, such as chemical corrosion method, grinding and polishing method, etc., each have their own advantages and disadvantages. Among them, the chemical corrosion method corrodes the surface of polysilicon by inorganic acid and alkali or organic acid and alkali solution to obtain the microstructure characterization sample of polysilicon. This method is simple to operate and can be corroded by immersion, but there are acid and alkali residues, it is not environmentally friendly, and it cannot meet the simultaneous observation of multiple morphological features. The grinding and polishing method generally includes grinding polysilicon samples and polishing polysilicon samples. Through the combination of multiple grinding processes and multiple polishing processes, the shortcomings of the chemical corrosion method can be overcome, and the microstructure characterization samples of polysilicon that meet the multi-scale structure observation can be obtained. It is the development trend of the preparation technology of polysilicon microstructure characterization samples. However, the samples obtained by the existing grinding and polishing methods are still difficult to meet the observation of the microstructure at a specific position in polycrystalline silicon, and it is impossible to obtain samples with a surface effect close to that of a non-destructive state. Summary of the invention
[0003] In view of the above problems, the present invention provides a method for preparing polysilicon microstructure characterization samples at a fixed point.
[0004] The purpose of the present invention is achieved through the following technical solutions:
[0005] A method for preparing a polycrystalline silicon microstructure characterization sample at a fixed point, comprising:
[0006] preparing polycrystalline silicon samples;
[0007] The polysilicon sample is polished and leveled with sandpaper;
[0008] Mechanical polishing and ion polishing are performed on the polycrystalline silicon sample obtained by sandpaper grinding;
[0009] The polysilicon samples obtained by mechanical polishing and ion polishing are subjected to micron-level fixed-point ion polishing to obtain polysilicon microstructure characterization samples.
[0010] Furthermore, in the preparation of the polysilicon sample, the original polysilicon is cut along the radial direction to obtain a fan-shaped or long strip block polysilicon sample.
[0011] Further, the sandpaper polishing of the polysilicon sample comprises:
[0012] The polysilicon sample was polished and leveled several times using sandpaper with a first-grade sand grain diameter;
[0013] The polysilicon sample was polished and leveled several times using sandpaper with a secondary grit diameter;
[0014] Wherein, the sandpaper with the secondary sand grain diameter is smaller than the primary sand grain diameter.
[0015] Furthermore, the sandpaper with the first-level sand grain diameter is used to polish the polysilicon sample for multiple times to make it smooth, and the grain size of the sandpaper is the same or different during each polishing;
[0016] The sandpaper with the secondary sand grain diameter is used to polish the polysilicon sample for multiple times to make it smooth, and the grain size of the sandpaper is the same or different during each polishing;
[0017] The diameter of the primary sand particles is 12.5 μm to 31.25 μm; the diameter of the secondary sand particles is 3.125 μm to 10.415 μm.
[0018] Furthermore, the polysilicon sample obtained by sandpaper polishing is subjected to mechanical polishing and ion polishing, comprising:
[0019] The polycrystalline silicon sample obtained by sandpaper polishing is polished using a diamond polishing liquid until the polycrystalline silicon sample presents a mirror effect under an optical microscope;
[0020] The polycrystalline silicon sample obtained by diamond polishing is polished using a silicon dioxide polishing liquid until the polycrystalline silicon sample presents a matte effect under an optical microscope;
[0021] The polysilicon sample obtained by silicon dioxide polishing is ion polished by using an ion thinning instrument until the polysilicon sample presents a mirror effect under an optical microscope.
[0022] Furthermore, the particle size of diamond in the diamond polishing liquid is 0.2-0.1 μm.
[0023] Furthermore, the particle size of silicon dioxide in the silicon dioxide polishing liquid is 0.08-0.01 μm.
[0024] Furthermore, when the ion thinning instrument performs ion polishing on the polysilicon sample obtained by silicon dioxide polishing, the electron gun has an operating voltage of 3-4 kV, and the angle between the electron gun and the surface of the block sample is 12-18°.
[0025] Furthermore, the polysilicon sample obtained by mechanical polishing and ion polishing is subjected to micron-level fixed-point ion polishing, comprising:
[0026] Using a Xe ion beam with an energy threshold or greater to perform coarse ion thinning on a polysilicon sample obtained by mechanical polishing and ion polishing;
[0027] The polysilicon sample obtained by coarse ion thinning was subjected to fine ion thinning using multiple Ar ion beams below the energy threshold.
[0028] Furthermore, the energy threshold is 6 kV.
[0029] Further, the coarse ion thinning time is 25-35min;
[0030] The coarse ion thinning time is 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min or 35 min.
[0031] Furthermore, the total time of the fine ion thinning is 25-35 minutes.
[0032] The total time for the fine ion thinning is 25 min, 26 min, 27 min, 28 min, 29 min, 30 min, 31 min, 32 min, 33 min, 34 min or 35 min.
[0033] Beneficial effects of the present invention:
[0034] A method for preparing a polysilicon microstructure characterization sample at a fixed point of the present invention adopts a combination of mechanical polishing, ion polishing and micron-level fixed-point ion polishing processes to obtain a completely non-destructive observation sample, and the sample can meet the observation of the microstructure at a specific position;
[0035] The present invention first obtains a sample with no scratches on the polished surface under an electron microscope on the basis of mechanical polishing and ion polishing processes. On this basis, the micron-level fixed-point ion polishing process proposed by the present invention is adopted, that is, a multi-beam focused ion beam is used to perform coarse ion thinning polishing and fine ion thinning polishing. The controllability of the polishing position and the polishing energy during focused ion beam polishing is utilized to achieve fixed-point polishing on the microscopic size of the sample surface. Not only is the sample with a surface effect close to a lossless state successfully obtained, but also the microstructure at a specific position in the polysilicon (such as the microstructure at the interface between the polysilicon substrate and the silicon core) is presented on the surface close to a lossless state, thereby solving the problems mentioned in the background technology.
[0036] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 The electron microscope scanning image of the polycrystalline silicon microstructure characterization sample prepared according to Example 1 of the present invention is shown;
[0039] Figure 2 A flow chart showing a method for preparing polysilicon microstructure characterization samples at a fixed point according to Embodiment 1 of the present invention is shown;
[0040] Figure 3 The appearance image and electron microscope scanning image of the polycrystalline silicon microstructure characterization sample prepared according to Comparative Example 1 of the present invention are shown. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The diamond polishing liquid and silicon dioxide polishing liquid used for polishing in the following examples are both purchased from the market, wherein the mass concentration of diamond in the diamond polishing liquid is 2% to 3%, and the mass concentration of silicon dioxide in the silicon dioxide polishing liquid is 5%.
[0043] Example 1
[0044] like Figure 2 As shown, according to a method for preparing a polysilicon microstructure characterization sample at a fixed point according to an embodiment of the present invention, the specific steps are as follows:
[0045] Step 1: Preparation of polysilicon samples:
[0046] First, a large block of 8-12 inch polysilicon is cut from the silicon core outward into fan-shaped or long strip block samples; on the cut block samples, the direction is marked from the silicon core outward to observe the polysilicon structure from the core to the outside;
[0047] Step 2: Polishing:
[0048] a. First, use sandpaper with a grit diameter of 32 μm to grind the cut block sample for 0.5 h, then use sandpaper with a grit diameter of 15 μm to grind for another 0.5 h, and then use sandpaper with a grit diameter of 12 μm to grind for another 0.5 h. After grinding, under an optical microscope, it is observed that the scratch direction and depth of the 12 μm sandpaper are consistent, and the previous scratches can be covered;
[0049] b. Use sandpaper with a grit diameter of 5 μm to grind the cut block sample for 0.5 h, then use sandpaper with a grit diameter of 5 μm to grind for another 0.5 h, and then use sandpaper with a grit diameter of 3.125 μm to grind for another 0.5 h. After grinding, it is observed under an optical microscope that the scratch direction and depth of the 3.125 μm sandpaper are consistent, and the previous scratches can be covered. After grinding, a preliminary mirror effect appears;
[0050] Step 3: Mechanical polishing and ion polishing:
[0051] a. Place the polishing cloth on the polishing machine and use diamond polishing liquid with a particle size of 0.1μm to polish the block sample for 20 minutes; polish until the scratch direction and depth of the block sample after polishing with the diamond polishing liquid with a particle size of 0.1μm are consistent under an optical microscope, and a mirror effect appears;
[0052] b. Place the polishing cloth on the polishing machine and use 0.01μm silica polishing liquid to polish the block sample for 20 minutes. Polish until, under an optical microscope, it is observed that the scratches made by the 0.01μm silica polishing liquid on the block sample are consistent in direction and depth, the surface presents a matte effect, and the force of mechanical grinding and polishing is sufficient to prevent the block sample from tilting and normal force.
[0053] c. Use an ion thinning instrument to re-polish the surface of the polished block sample. The working voltage of the electron gun is 3.6kV, the angle between the electron gun and the block sample surface is 15°, and the polishing time is 15-30min. After polishing, there are no scratches on the polished surface of the block sample under an electron microscope, and the surface presents a clean mirror effect.
[0054] Step 4: Fixed-point ion polishing:
[0055] Under a multi-beam focused ion beam electron microscope, an electron beam is used to observe the sample surface, select features at the micro-nano scale, and use a multi-beam focused ion beam electron microscope to perform micron-level fixed-point plane or cross-sectional ion polishing on block samples after mechanical grinding and polishing. The specific polishing process includes:
[0056] Coarse ion thinning: 6kVXe ions were used for coarse ion thinning for 30 min;
[0057] Fine ion thinning: 4kVAr ions are subjected to fine ion thinning for 10 minutes, 3kVAr ions are subjected to fine ion thinning for 10 minutes, and 2kVAr ions are subjected to fine ion thinning for 10 minutes;
[0058] In addition, during the process of micron-level fixed-point planar or cross-sectional ion polishing of block samples after mechanical grinding and polishing by multi-beam focused ion beam electron microscopy, the sample surface is observed under the electron beam to be free of structure and stress defects, so as to meet the full-scale observation from macro to meso to micro, and obtain polycrystalline silicon microstructure characterization samples.
[0059] The obtained polysilicon microstructure characterization sample was observed by scanning electron microscope, and the obtained observation image is as follows: Figure 1 As shown, Figure 1 In the figure a, the complex polycrystalline structure of the polysilicon matrix is shown. Figure 1 Figure b shows the complex microstructure near the polysilicon substrate-silicon core interface.
[0060] from Figure 1 It shows that the polycrystalline silicon microstructure characterization sample obtained in Example 1 can clearly observe the microstructure at a specific position of the polycrystalline silicon.
[0061] Example 2
[0062] A method for preparing polysilicon microstructure characterization samples at a fixed point, the specific steps are as follows:
[0063] Step 1: Preparation of polysilicon samples:
[0064] First, a large block of 8-12 inch polysilicon is cut from the silicon core outward into fan-shaped or long strip block samples; on the cut block samples, the direction is marked from the silicon core outward to observe the polysilicon structure from the core to the outside;
[0065] Step 2: Polishing:
[0066] a. First, use sandpaper with a grit diameter of 15 μm to grind the cut block samples in turn for 1 hour. Under an optical microscope, it is observed that the scratch direction and depth of the sandpaper with a grit diameter of 15 μm are consistent.
[0067] b. Use sandpaper with a sand grain diameter of 3.125μm to grind the cut block samples in turn for 1 hour. Under an optical microscope, it is observed that the scratch direction and depth of the 3.125μm sand grain diameter sandpaper are consistent, and the previous scratches can be covered. After grinding, a mirror effect appears initially.
[0068] Step 3: Mechanical polishing and ion polishing:
[0069] a. Place the polishing cloth on the polishing machine and use diamond polishing liquid with a particle size of 0.15μm to polish the block sample for 20 minutes; polish until the direction and depth of the scratches on the block sample after polishing with the diamond polishing liquid with a particle size of 0.15μm are consistent under an optical microscope, and a mirror effect appears;
[0070] b. Place the polishing cloth on the polishing machine and use 0.04μm silica polishing liquid to polish the block sample for 20 minutes; polish until the direction and depth of the scratches made by the 0.04μm silica polishing liquid on the block sample are consistent under an optical microscope, the surface presents a matte effect, and the mechanical grinding and polishing force is sufficient to prevent the block sample from tilting and normal force;
[0071] c. Use an ion thinning instrument to re-polish the surface of the polished block sample. The working voltage of the electron gun of the ion thinning instrument is 3.6kV, the angle between the electron gun and the block sample surface is 15°, and the polishing time is 25min. After polishing, there are no scratches on the polished surface of the block sample under an electron microscope, and the surface presents a clean mirror effect.
[0072] Step 4: Fixed-point ion polishing:
[0073] Under a multi-beam focused ion beam electron microscope, an electron beam is used to observe the sample surface, select features at the micro-nano scale, and use a multi-beam focused ion beam electron microscope to perform micron-level fixed-point plane or cross-sectional ion polishing on block samples after mechanical grinding and polishing. The specific polishing process includes:
[0074] Coarse ion thinning: 6kVXe ions were used for coarse ion thinning for 30 min;
[0075] Fine ion thinning: 4kVAr ions are subjected to fine ion thinning for 10 minutes, 3kVAr ions are subjected to fine ion thinning for 10 minutes, and 2kVAr ions are subjected to fine ion thinning for 10 minutes;
[0076] In addition, during the process of micron-level fixed-point planar or cross-sectional ion polishing of block samples after mechanical grinding and polishing by multi-beam focused ion beam electron microscopy, the sample surface is observed under the electron beam to be free of structure and stress defects, which meets the full-scale observation from macro to meso to micro, and can obtain polycrystalline silicon microstructure characterization samples.
[0077] Example 3
[0078] A method for preparing polysilicon microstructure characterization samples at a fixed point, characterized in that the specific steps are as follows:
[0079] Step 1: Preparation of polysilicon samples:
[0080] First, a large block of 8-12 inch polysilicon is cut from the silicon core outward into fan-shaped or long strip block samples; on the cut block samples, the direction is marked from the silicon core outward to restrict the subsequent grinding and polishing direction;
[0081] Step 2: Polishing:
[0082] a. First, use sandpaper with a grit diameter of 32 μm to grind the cut block samples in turn for 0.5-1.5 hours. Under an optical microscope, it is observed that the scratch direction and depth of the sandpaper with a grit diameter of 32 μm are consistent.
[0083] b. Use sandpaper with a sand grain diameter of 3.125μm to grind the cut block samples in turn for 1 hour. Under an optical microscope, it is observed that the scratch direction and depth of the 3.125μm sand grain diameter sandpaper are consistent, and the previous scratches can be covered. After grinding, a mirror effect appears initially.
[0084] Step 3: Mechanical polishing and ion polishing:
[0085] a. Place the polishing cloth on the polishing machine and use a diamond polishing liquid with a particle size of 0.2μm to polish the block sample for 20 minutes; polish until the direction and depth of the scratches on the block sample after polishing with the diamond polishing liquid with a particle size of 0.2μm are consistent under an optical microscope, and a mirror effect appears;
[0086] b. Place the polishing cloth on the polishing machine and use a 0.02μm silica polishing liquid to polish the block sample for 20 minutes. Polish until the direction and depth of the scratches made by the 0.02μm silica polishing liquid on the block sample are consistent under an optical microscope, the surface presents a matte effect, and the mechanical grinding and polishing force is sufficient to prevent the block sample from tilting and normal force.
[0087] c. Use an ion thinning instrument to re-polish the surface of the polished block sample. The working voltage of the electron gun of the ion thinning instrument is 3.6kV, the angle between the electron gun and the block sample surface is 15°, and the polishing time is 25min. After polishing, there are no scratches on the polished surface of the block sample under an electron microscope, and the surface presents a clean mirror effect.
[0088] Step 4: Fixed-point ion polishing:
[0089] Under a multi-beam focused ion beam electron microscope, an electron beam is used to observe the sample surface, select features at the micro-nano scale, and use a multi-beam focused ion beam electron microscope to perform micron-level fixed-point plane or cross-sectional ion polishing on block samples after mechanical grinding and polishing. The specific polishing process includes:
[0090] Coarse ion thinning: 6kVXe ions were used for coarse ion thinning for 30 min;
[0091] Fine ion thinning: 4kVAr ions are subjected to fine ion thinning for 10 minutes, 3kVAr ions are subjected to fine ion thinning for 10 minutes, and 2kVAr ions are subjected to fine ion thinning for 10 minutes;
[0092] In addition, during the process of micron-level fixed-point planar or cross-sectional ion polishing of block samples after mechanical grinding and polishing by multi-beam focused ion beam electron microscopy, the sample surface is observed under the electron beam to be free of structure and stress defects, which meets the full-scale observation from macro to meso to micro, and can obtain polycrystalline silicon microstructure characterization samples.
[0093] Comparative Example 1
[0094] The method for preparing a polycrystalline silicon microstructure characterization sample is as follows: compared with Example 1, the fixed-point ion polishing step of step 4 is deleted, and the rest is the same.
[0095] The sample obtained in Comparative Example 1 was scanned by electron microscope, and the obtained picture is shown in Figure 3 ,in, Figure 3 a is the appearance picture of the characterization sample obtained in Comparative Example 1, Figure 3 b is a scanning image of the whole characterization sample obtained in Comparative Example 1 under a scanning electron microscope. Figure 3 Figure c is one of the local scanning images of the sample obtained in Comparative Example 1 under a scanning electron microscope. Figure 3 Figure d is one of the local scanning images of the characterization sample obtained in Comparative Example 1 under a scanning electron microscope;
[0096] from Figure 3 It can be seen that for the sample of comparative example 1, when it has not been polished at a fixed point, the surface flatness of the material is relatively general, and there are impurities such as black spots to varying degrees (specifically, Figure 3 d), which indicates that there is an inevitable polishing error during the polishing operation of Comparative Example 1. Figure 3 The fluctuations in the middle field of view (such as Figure 3 Medium c and Figure 3 d), which indicates that the polishing operation of Comparative Example 1 is not able to be completely polished, which may affect the observed results. Figure 1 As shown, the sample surface obtained by the method for preparing polysilicon microstructure characterization samples at a fixed point provided in Example 1 of the present invention is very smooth and has a nearly lossless structure, and can restore the surface state of the sample to the greatest extent.
[0097] Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent substitutions for some of the technical features therein; and these modifications or substitutions do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing polycrystalline silicon microstructure characterization samples at a fixed point, characterized in that: include: preparing polycrystalline silicon samples; The polysilicon sample is polished and leveled with sandpaper; Mechanical polishing and ion polishing are performed on the polycrystalline silicon sample obtained by sandpaper grinding; The polysilicon samples obtained by mechanical polishing and ion polishing are subjected to micron-level fixed-point ion polishing to obtain polysilicon microstructure characterization samples.
2. The method for preparing polycrystalline silicon microstructure characterization samples at a fixed point according to claim 1, characterized in that: The method of sandpaper grinding the polysilicon sample to make it smooth comprises: The polysilicon sample was polished and leveled several times using sandpaper with a first-grade sand grain diameter; The polysilicon sample was polished and leveled several times using sandpaper with a secondary grit diameter; Wherein, the diameter of the secondary sand particles is smaller than the diameter of the primary sand particles.
3. The method for preparing polycrystalline silicon microstructure characterization samples at a fixed point according to claim 2, characterized in that: The sandpaper with the first-level sand grain diameter is used to polish the polysilicon sample for multiple times to make it smooth, and the grain size of the sandpaper is the same or different during each polishing; The sandpaper with the secondary sand grain diameter is used to polish the polysilicon sample for multiple times to make it smooth, and the grain size of the sandpaper is the same or different during each polishing; The diameter of the primary sand particles is 12.5 μm to 31.25 μm; the diameter of the secondary sand particles is 3.125 μm to 10.415 μm.
4. The method for preparing polysilicon microstructure characterization samples at a fixed point according to claim 1, characterized in that: The method of mechanically polishing and ion polishing the polysilicon sample obtained by sandpaper polishing comprises: The polycrystalline silicon sample obtained by sandpaper polishing is polished using a diamond polishing liquid until the polycrystalline silicon sample presents a mirror effect under an optical microscope; The polycrystalline silicon sample obtained by diamond polishing is polished using a silicon dioxide polishing liquid until the polycrystalline silicon sample presents a matte effect under an optical microscope; The polysilicon sample obtained by silicon dioxide polishing is ion polished by using an ion thinning instrument until the polysilicon sample presents a mirror effect under an optical microscope.
5. The method for preparing polycrystalline silicon microstructure characterization samples at a fixed point according to claim 4, characterized in that: The particle size of diamond in the diamond polishing liquid is 0.2-0.1 μm.
6. The method for preparing polycrystalline silicon microstructure characterization samples at a fixed point according to claim 4, characterized in that: The particle size of the silicon dioxide in the silicon dioxide polishing liquid is 0.08-0.01 μm.
7. The method for preparing polycrystalline silicon microstructure characterization samples at a fixed point according to claim 4, characterized in that: When the ion thinning instrument performs ion polishing on the polysilicon sample obtained by polishing silicon dioxide, the electron gun has a working voltage of 3-4 kV, and the angle between the electron gun and the surface of the block sample is 12-18°.
8. The method for preparing polycrystalline silicon microstructure characterization samples at a fixed point according to any one of claims 1 to 7, characterized in that: The method of performing micron-level fixed-point ion polishing on the polysilicon sample obtained by mechanical polishing and ion polishing comprises: Using a Xe ion beam with an energy threshold or greater to perform coarse ion thinning on a polysilicon sample obtained by mechanical polishing and ion polishing; The polysilicon sample obtained by coarse ion thinning was subjected to fine ion thinning using multiple Ar ion beams below the energy threshold.
9. The method for preparing polycrystalline silicon microstructure characterization samples at a fixed point according to claim 8, characterized in that: The energy threshold is 6 kV, and the coarse ion thinning time is 25-35 min.
10. The method for preparing polycrystalline silicon microstructure characterization samples at a fixed point according to claim 8, characterized in that: The total time for the fine ion thinning is 25-35 minutes.
Citation Information
Cited By
Method for detecting quality of polycrystalline silicon for zone melting based on multi-parameter coupling
CN121049312A
Preparation method of silicon through hole cross section sample of bonding wafer
CN121540515A
